Association Between Gut Microbiome and Frailty in the Older Adult Population in Korea. (13th January 2021) - Lim, Mi Young; Hong, Seungpyo; Kim, Jung-Ha; Nam, Young-Do
Abstract: Frailty is a common geriatric syndrome associated with the risk of adverse health outcomes. Recently, 2 key pathophysiological characteristics of frailty, altered energy metabolism and dysregulated immunity, have been reported to be associated with gut microbiome dysbiosis, indicating that the gut microbiome plays a role in frailty. However, few studies have directly examined the relationship between the gut microbiome and frailty. Here, we investigated the association of frailty measures with the gut microbiome using 16S rRNA gene sequencing data obtained from the fecal samples of 176 Korean older adults. Overall frailty was scored using the Korean Frailty Index (FI). Grip strength and Geriatric Depression Scale (GDS) scores were used as physical and mental frailty measures, respectively. In contrast to age, metabolic, and inflammatory biomarkers, the frailty measures were associated with interindividual variations in microbial composition (false discovery rate [FDR] < 0.2). Both FI and GDS scores were negatively associated with microbial diversity (FDR < 0.2). Frailty measures showed distinct associations with specific microbial taxa and metabolic functions. Particularly, the Bacteroides enterotype was found only in subjects categorized in the frail group. Moreover, we observed that the abundance of beneficial taxa, such as Prevotella copri and Coprococcus eutactus, was reduced in frailer individuals, whereas that of detrimental taxa, such as Bacteroides fragilis and Clostridium hathewayi, was increased (FDR < 0.2). Our findings suggest that the gut microbiome can be used an indicator of an increased risk of frailty or a target for improving health in frail older adults.